Evaluation of ECG Interpretation Results Obtained by Computer and Cardiologists - Willems, J. L.; Abreu-Lima, C.; Arnaud, P.; Brohet, C. R.; Denis, B.; Gehring, J.; Graham, I.; van Herpen, G.; Machado, H.; Michaelis, J.; Moulopoulos, S. D. (Methods of Information in Medicine, 1990)
In an international project investigators from 25 institutes are trying to establish a common reference library and evaluation methods for testing the diagnostic performance of various ECG computer programs and of cardiologists, based on ECG-independent clinical information. A first set of 500 validated ECGs was collected and analyzed by fifteen different computer programs and nine cardiologists, seven of who analysed the ECG and five the VCG. A coding scheme was used to map individual diagnostic statements onto a common set. Combined program and referee results were obtained by weighted averaging. Preliminary results indicate that the classification accuracy of several programs can still be improved. However, it was also apparent that the results of the best 12-lead ECG computer programs proved to be almost as accurate as the best of seven cardiologists in classifying seven main disease categories, i.e., normal, left, right and biventricular hypertrophy, anterior, inferior and combined myocardial infarction. Evaluation of rhythm statements and conduction disturbances was not included in the study. The data collection is still being pursued in order to reach over 1,000 cases. In this way a common diagnostic database is being established for comparative testing of diagnostic computer programs. This should lead to consumer protection and improve the accuracy and reliability of computerized electrocardiography.
Keywords: ECG Classification; Computerized Electrocardiography; Diagnostic Accuracy; Performance Testing